Trevor’s Disease: A Literature Review regarding Classification, Treatment, and Prognosis apropos of a Case - Georgios Arealis; Vassilios S. Nikolaou; Andrew Lacon; Neil Ashwood; Keith Hayward; Charalampos Karagkevrekis (Case Reports in Orthopedics)
Background. Dysplasia epiphysealis hemimelica (DEH) is rare and its main characteristic is osteochondromas of the epiphysis of long bones. Methods. We report a case of DEH of the ankle in an 8-year-old boy that was resected in 2005. Additionally we collect all the reported cases of DEH. The literature is reviewed regarding the treatment, prognosis, long term function, and patterns and areas affected by DEH. Results. In our case no complications were noted and our patient remains asymptomatic. Reviewing the literature we found that 73 authors have reported 144 cases from 1926 to 2013. We propose and describe a new classification that correlates with prognosis. According to our classification DEH is classified as types 1 with single lower limb involvement, 2 with multiple lower limb, 3 with single upper limb, 4 with multiple upper limb, 5 with upper and lower limb, and 6 with spine. Conclusions. All single lesions should be followed up and if indicated a whole body nuclear bone scan can be useful in identifying the existence of multiple affected joints. Type 1 lesions have better prognosis than 2 and have less chances of developing OA even if not resected. Resection, even if partial, can be a successful treatment for DEH.